Doughnut economics : seven ways to think like a 21st century economist - Raworth, Kate (London : Random House Business Books, 2017)
Raworth sets out seven key ways to fundamentally reframe our understanding of what economics is and does. Along the way, she points out how we can break our addiction to growth; redesign money, finance, and business to be in service to people; and create economies that are regenerative and distributive by design. Named after the now-iconic doughnut? image that Raworth first drew to depict a sweet spot of human prosperity (an image that appealed to the Occupy Movement, the United Nations, eco-activists, and business leaders alike), Doughnut Economics offers a radically new compass for guiding global development, government policy, and corporate strategy, and sets new standards for what economic success looks like.
Includes bibliographical references (pages 259-296) and index.
nmn 10/01/2019, ijb, 28/01/2019
Loans
Keywords: Economics; Economic forecasting; Economics -- History